A scrabble-inspired physics learning tool to enhance understanding and retention of newton’s laws of motion - Mohd Napiah, Noorezal Atfyinna; Rosli, Siti Azlina; Abdul Hamid, Haslinda (2025)
Despite the increasing use of digital tools and multimedia in classrooms, many students continue to struggle with understanding and remembering fundamental physics concepts, particularly Newton’s Laws of Motion. These topics involve abstract ideas and scientific terms that are often difficult to grasp through traditional teaching methods. Recognizing these challenges, this innovation introduces a Scrabble-inspired physics learning tool designed to improve memory retention and conceptual understanding of Newton’s Laws of Motion in an engaging and meaningful way. This interactive, wordbased game promotes active recall and deeper learning through repeated exposure to physics terms and definitions. The tool is specifically developed for diploma-level physics students but is adaptable across various educational settings, including secondary school, matriculation, and pre-university programmes. In addition to improving conceptual retention, the tool also supports the development of 21st-century skills such as critical thinking and communication. It offers educators a creative and effective way to enhance physics instruction in the classroom. Ultimately, this tool helps students learn more effectively, understand concepts more clearly, and maintain lasting interest in physics.